ICT Memungkinkan Orang Bekerja dari Rumah: Studi Kasus pada Bank dan Kursus Online - Lisanti, Yuliana (Bina Nusantara University, 2014)
The Information technology and telecommunications (ICT - Information and Communication Technology) utilization to facilitate the home worker or teleworker has started being implemented in many companies. The study showed that the home worker offers benefits such as offering the flexibility to improve employee?s work-life balance, cost savings from hot desking implementation, which also support the clean desk policy implementation. In addition, the government needs to encourage firms to adopt the work from home concept, as it can helps to facilitate housewives hence they can have additional income, furthermore, the home worker could help to solve social problems such as traffic congestion in major cities.